Impak konotasi budaya terhadap leksis: satu kajian semantik berasaskan korpus, ke atas perkataan perempuan dan wanita (Jurnal Bahasa, 2005)
The use of repeated phrases and conventional ways of talking form a constellation of meanings that reflects the typical meanings that lexical forms or expressions have. In other words, they reflect meanings that are repeatedly expressed in a discourse community. Meanings that words inherit due to recurrent occurrence are cultural connotations that can reflect the social reality of the community. As such, the analysis of recurrent wordings is of central importance in the study of language and ideology, and can provide empirical evidence of how the culture is encoded in lexis. This article reports on a study of the cultural connotations of "perempuan" and "wanita" by analysing the discourse, that is the vocabulary employed whenever the words are used. The two words are considered important cultural keywords in the Malay language. They have similar denotations but seen to possess different reputation due to the connotations that are inherited. The study used empirical evidence to investigate this by examining the semantic prosody and the cultural connotations of both words. This was achieved by employing a computrerised corpus-based co/locational analysis of the words. This article reports on the analysis that was carried out and discusses the nuances that are found in both words due to usage, and attempts to link the findings to the social and cultural changes that have taken place.